2021
DOI: 10.7150/jca.51407
|View full text |Cite
|
Sign up to set email alerts
|

Asparagus Polysaccharide inhibits the Hypoxia-induced migration, invasion and angiogenesis of Hepatocellular Carcinoma Cells partly through regulating HIF1α/VEGF expression via MAPK and PI3K signaling pathway

Abstract: Aim: Although there are so many treatment strategies used for hepatocellular carcinoma (HCC), the overall survival (OS) of HCC patients still remains very low. In our previous studies, asparagus polysaccharide (ASP) has been demonstrated to suppress proliferation, migration, invasion and angiogenesis of HCC cells under normoxic conditions in vitro. However, the inhibitory effects of ASP on the hypoxia-induced migration, invasion and angiogenesis of HCC cells still remain largely unexplored. Materials and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The anticancer activity of polysaccharide, saponin, and flavonoid extracts from ASP has been reported in various cancers, such as lung and bladder cancer ( Bilušić et al, 2019 ), liver cancer ( Cheng et al, 2021 ), and ovarian cancer ( Xu et al, 2021 ). Some studies have found that asparagus saponin extracts have significant cytotoxic effects on colorectal cancer cells ( Jaramillo-Carmona et al, 2018 ), and the results of Bousserouel ( Bousserouel et al, 2013 ) and others have shown in more detail that methanolic extracts of ASP can induce apoptosis by activating the TRAIL death receptor pathway in SW480 and SW620 human colon adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticancer activity of polysaccharide, saponin, and flavonoid extracts from ASP has been reported in various cancers, such as lung and bladder cancer ( Bilušić et al, 2019 ), liver cancer ( Cheng et al, 2021 ), and ovarian cancer ( Xu et al, 2021 ). Some studies have found that asparagus saponin extracts have significant cytotoxic effects on colorectal cancer cells ( Jaramillo-Carmona et al, 2018 ), and the results of Bousserouel ( Bousserouel et al, 2013 ) and others have shown in more detail that methanolic extracts of ASP can induce apoptosis by activating the TRAIL death receptor pathway in SW480 and SW620 human colon adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…ASP has nourishing, moistening, fire-clearing, cough-suppressing, and intestinal effects and exerts anti-inflammatory, antioxidant, anti-aging, immunity-enhancing, and anti-tumor pharmacological effect ( Samad et al, 2014 ; Lei et al, 2017 ; Cheng et al, 2019 ; Sun et al, 2020 ). Recent studies have reported that ASP polysaccharides can inhibit hypoxia-induced hepatocellular carcinoma cell migration, invasion, and angiogenesis by regulating hypoxia inducible factor alpha (HIF-1α) and vascular endothelial growth factor (VEGF) expression through mitogen activated protein kinase (MAPK) and phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) signaling pathways ( Cheng et al, 2021 ). In addition, ASP-derived exosome-like nanovesicles could inhibit hepatocellular carcinoma cell proliferation, induce apoptosis, and inhibit tumor growth without significant side effects in mice ( Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several polysaccharides could block HCC angiogenesis by downregulating hypoxia-inducible factor 1α (HIF-1α) and vascular endothelial growth factors (VEGFs). Moreover, asparagus and dandelion polysaccharides could inhibit MAPK and PI3K signaling pathways to block tumor angiogenesis [ 82 , 83 , 84 ].…”
Section: Polysaccharides In Different Liver Diseasesmentioning
confidence: 99%
“…The researchers also observed a decrease in the protein levels of HIF-1α and its downstream vascular endothelial growth factor (VEGF) after ASP treatment. 133 Low molecular weight fucoidan (LMWF), extracted from brown algae, has been reported to inhibit tumor growth and capillary formation of tumors in bladder cancerbearing mice. Exposure of bladder cancer cells T24 to LMWF inhibited the accumulation of HIF-1 and the secretion of VEGF produced under hypoxia.…”
Section: Cancermentioning
confidence: 99%